Answer:
Shift the graph of y = x2 left 13 units and then up 6 units.
Step-by-step explanation:
Answer:
Step-by-step explanation:
y = ax² + bx + c
~~~~~~~
(4, - 2), (8, 6), (2, 0)
a(4²) + b(4) + c = - 2
a(8²) + b(8) + c = 6
a(2²) + b(2) + c = 0
16a + 4b + c = - 2 .............. <em>(1)</em>
64a + 8b + c = 6 ............... <em>(2)</em>
4a + 2b + c = 0 ................. <em>(3)</em>
a = 0.5 ; b = - 4 ; c = 6
<em>y = 0.5x² - 4x + 6</em>
Part A: (0, 6), (6, 0)
Part B: (0,6)
Part C: (6, 0)
Part D: [ 4, ∞ )
45 x 0.44 = ?
30 x 0.44 = ?
Then add the two answers together.
Answer: -3x + 4, (2,-2)
Step-by-step explanation:
First, you want to get y alone on one side.
3x + y = 4
-4 -4 subtract 4 to get it on the left side.
-y -y subtract y to get it alone on the right side.
Your'e left with 3x - 4 = -y divide the whole equation by -1 do get a pos y
You then have y = -3x + 4. That's the first part of your answer.
To get the second part plug in (-3x + 4) into the y of the first equation, this is the substitution part.
-2x + 5(-3x+4) =-14 distribute the 5... -2x - 15x +20 = -14
add your like terms ( x and x) -17x + 20 = -14
Isolate your x by subtracting the 20, both sides -20 -20
-17x = -34 divide both side by 17 you get x = 2 (---- this is your first coordinate in the pair in your answer. To get the y do the same but solve for y instead of x.